Effects of UV filters 2-ethylhexyl 4-methoxycinnamate and benzophenone-3 on in vitro steroidogenesis during oocyte maturation of the longchin goby, Chasmichthys dolichognathus - Woo, Heewon; Baek, Hea Ja; Hwang, In Joon (Frontiers in Marine Science, 2025)
We investigated the estrogenic effects of 2-ethylhexyl 4-methoxycinnamate (EHMC) and benzophenone-3 (BP-3) on steroidogenesis in maturing oocytes of the longchin goby. Oocytes with 0.77-, 0.82-, and 0.87-mm diameters were incubated with EHMC (0.5–500 ng/mL) or BP-3 (0.5–500 ng/mL) for 24 h with [³H]17α-hydroxyprogesterone as a precursor. The major steroid metabolites were separated and identified as androstenedione, testosterone (T), estradiol-17β (E2), estrone, and 17,20β-dihydroxy-4-pregnen-3-one (17α20βP). The E2 metabolite was significantly increased at 5 and 0.5 ng/mL of EHMC in 0.82- and 0.87-mm-diameter oocytes, respectively. Furthermore, it was increased significantly at 5 ng/mL of BP-3 in the oocytes of 0.87 mm. In addition, 5, 50, and 500 ng/mL of EHMC increased the ratio of E2/17α20βP in the oocytes of 0.82 mm. 0.5 ng/mL of BP-3 increased the ratio of E2/T in the oocytes of 0.87 mm. These results suggest that EHMC and BP-3 have a potential estrogenic activity in the steroidogenic shift process, vitellogenic stage to final maturation stage.